2012
DOI: 10.1080/02786826.2011.635726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Filter and Wall Deposits From Samplers Used to Collect Airborne Lead-Containing Dusts at Field Sites

Abstract: and 37 mm closed face cassette samplers (CFC) were deployed where occupational exposures to lead-containing dusts were known to occur. Discrete particle analyses of wall and filter deposits were performed by Scanning Electron Microscopy-Energy Dispersive Xray Spectrometry (SEM-EDX). From the elemental composition and projected area diameter of each particle a density, volume, and mass were calculated, and a mass-weighted size distribution for each filter and corresponding wall deposit determined. Comparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…(2) This underestimation results from a significant accumulation of sampled particles on internal sampler walls that is not included in many analytical procedures. (2,3) A significant mass of material, up to or even exceeding that found on the filter, can be deposited on the internal surfaces of the air sampling device during sampling and subsequent handling. (2)(3)(4)(5)(6)(7)(8) Sampling for airborne metal dusts in occupational environments requires the evaluation of all particles entering the sampler, whether or not they are found on the filter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) This underestimation results from a significant accumulation of sampled particles on internal sampler walls that is not included in many analytical procedures. (2,3) A significant mass of material, up to or even exceeding that found on the filter, can be deposited on the internal surfaces of the air sampling device during sampling and subsequent handling. (2)(3)(4)(5)(6)(7)(8) Sampling for airborne metal dusts in occupational environments requires the evaluation of all particles entering the sampler, whether or not they are found on the filter.…”
Section: Introductionmentioning
confidence: 99%
“…(2,3) A significant mass of material, up to or even exceeding that found on the filter, can be deposited on the internal surfaces of the air sampling device during sampling and subsequent handling. (2)(3)(4)(5)(6)(7)(8) Sampling for airborne metal dusts in occupational environments requires the evaluation of all particles entering the sampler, whether or not they are found on the filter. (2)(3)(4)(5) Procedures to incorporate this material, such as wiping (4) or rinsing, (9) with the filter for subsequent analysis, are labor intensive.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a risk of underestimating actual exposures if only the filter is analyzed. Particles containing lead have shown no qualitative difference in the size distribution when aerosols deposit on the filter or on the internal surfaces of the cassette in controlled laboratory (Lee et al 2009) and field (Chisholm et al 2012) experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the issue has also been studied for airborne organic materials, including bacterial endotoxin [ 34 ], wood [ 35 ], and pharmaceutical dusts [ 22 ]; another relevant study reported results from investigations in thermosetting plastics, wood, paper, and animal breeding [ 36 ]. Except in the case of very large wood dust particles, there is no evidence to suggest that wall deposited particles are sufficiently different from those found on the collection substrate to warrant their exclusion [ 37 , 38 ]. Wall deposits are not limited to aerosol samplers for larger airborne particles but may also be found in samplers for finer particles [ 39 , 40 ].…”
Section: Recognition and Inclusion Of Sampler Wall Depositsmentioning
confidence: 99%